2017
DOI: 10.1177/1078155217694492
|View full text |Cite
|
Sign up to set email alerts
|

Rare incidence of tumor lysis syndrome in metastatic prostate cancer following treatment with docetaxel

Abstract: Tumor lysis syndrome is a serious and sometimes lethal complication of cancer treatment that is comprised of a set of metabolic disturbances along with clinical manifestations. Initiating chemotherapy in bulky, rapidly proliferating tumors causes rapid cell turnover that in turn releases metabolites into circulation that give rise to metabolic derangements that can be dangerous. This syndrome is usually seen in high-grade hematological malignancies. Less commonly, tumor lysis syndrome can present in solid tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In our review of the literature, we found nine cases of TLS occurring in patients with prostate cancer [2-10]. The majority of these cases involved the development of TLS after initiation of cancer-directed therapy [2-5, 8, 9]. Specifically, there were three cases of TLS after cytotoxic chemotherapy with either docetaxel or paclitaxel and two cases after androgen deprivation therapy (ADT), both with and without radiation therapy [2-5, 8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our review of the literature, we found nine cases of TLS occurring in patients with prostate cancer [2-10]. The majority of these cases involved the development of TLS after initiation of cancer-directed therapy [2-5, 8, 9]. Specifically, there were three cases of TLS after cytotoxic chemotherapy with either docetaxel or paclitaxel and two cases after androgen deprivation therapy (ADT), both with and without radiation therapy [2-5, 8].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these cases involved the development of TLS after initiation of cancer-directed therapy [2-5, 8, 9]. Specifically, there were three cases of TLS after cytotoxic chemotherapy with either docetaxel or paclitaxel and two cases after androgen deprivation therapy (ADT), both with and without radiation therapy [2-5, 8]. There was also one documented case of TLS after radiation therapy alone [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our case was similar in that there was recurrence with multiple metastasis and a regimen containing chemotherapeutic agents (platinum and taxane) was used. TLS associated with docetaxel has also been reported in only three cases: two patients with multiple metastatic prostate cancer ( Bhardwaj and Varma, 2017 ; Sorscher, 2004 ) and a patient with non-small-cell lung cancer ( Ajzensztejn et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%